The Pleiades Flare Stars in the Gaia Era - Hambaryan, V.; Ghazaryan, S.; Hambardzumyan, L.; Neuhaeuser, R.; Mirzoyan, A.; Tsvetkova, K. P.
We study the six dimensional arrangement of flare stars in the Pleiades cluster region using the third release of the Gaia–mission (Gaia DR3) and we provide preliminary, a new, original view of the spatial configuration of the flare “star-members” of the cluster.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture